EFEKTIVITAS MEDIA PROMOSI KESEHATAN DALAM PENINGKATAN PENGETAHUAN SISWA TENTANG BAHAYA SEKS BEBAS DI SMAS MARKUS MEDAN - Putranto Manalu; Dameria Gultom; Vera Prianggi Hutabarat; Sindy Andari; Villia Sitepu (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
The influence of the spread of sexual stimulation (pornography) through a bad social environment causes adolescent characters formed by the environment and the lack of information about the dangers of free sex both through audio-visual media brochures and others. This study aims to compare the effect of various health promotion media (leaflets, comics, and Whatsapp group applications) in increasing students' knowledge about the dangers of free sex at Markus Medan High School. The study design uses quasi-experimental (quasi-experimental) namely the pretest and posttest control group design to determine differences in knowledge that occur due to the influence of the treatment (intervention). The results showed an increase in adolescent knowledge scores by 2.53 points after being given counseling plus leaflets, counseling plus comics could increase adolescent knowledge scores by 5.46 points, and counseling plus WhatsApp given to adolescents could increase scores of adolescent knowledge about free sex by 2.70 points. The best method is counseling plus comics because it can change the highest knowledge score. The use of comics as a medium for health education for adolescents needs to be developed to prevent adolescents from the adverse effects of free sex and also the formation of a WhatsApp group for adolescents as well as health education content especially the adverse effects of free sex